Anti-Inflammatory Effects of the 35kDa Hyaluronic Acid Fragment (B-HA/HA35) - Jia X; Shi M; Wang Q; Hui J; Shofaro JH; Erkhembayar R; Hui M; Gao C; Gantumur MA (Dove Medical Press, 2023)
XiaoXiao Jia,1,2,* Ming Shi,3,* Qifei Wang,1,2 Jessica Hui,4 Joshua Hui Shofaro,1,2 Ryenchindorj Erkhembayar,5 Mizhou Hui,1,2 Chenzhe Gao,1 Munkh-Amgalan Gantumur1 1College of Life Science, Northeast Agricultural University, Harbin, People's Republic of China; 2College of Veterinary Medicine, Qingdao Agricultural University, Qingdao, People's Republic of China; 3School of Life Science and Technology, Harbin Institute of Technology, Harbin, People's Republic of China; 4Center for Cancer Cell Therapy, Stanford Cancer Institute, Stanford University School of Medicine, Stanford, CA, USA; 5Department of International Cyber Education, Graduate School, Mongolian National University of Medical Sciences, Ulaanbaatar, Mongolia*These authors contributed equally to this workCorrespondence: Mizhou Hui; Munkh-Amgalan Gantumur, Email huimizhou@163.com; mnkh.calm@gmail.comBackground: Hyaluronic acid (HA) and HA fragments interact with a variety of human body receptors and are involved in the regulation of various physiological functions and leukocyte trafficking in the body. Accordingly, the development of an injectable HA fragment with good tissue permeability, the identification of its indications, and molecular mechanisms are of great significance for its clinical application. The previous studies showed that the clinical effects of injectable 35kDa B-HA result from B-HA binding to multiple receptors in different cells, tissues, and organs. This study lays the foundation for further studies on the comprehensive clinical effects of injectable B-HA.Methods: We elaborated on the production process, bioactivity assay, efficacy analyses, and safety evaluation of an injectable novel HA fragment with an average molecular weight of 35 kDa (35 kDa B-HA), produced by recombinant human hyaluronidase PH20 digestion.Results: The results showed that 35 kDa B-HA induced human erythrocyte aggregation (rouleaux formation) and accelerated erythrocyte sedimentation rates through the CD44 receptor. B-HA application and injection treatment significantly promoted the removal of mononuclear cells from the site of inflammation and into the lymphatic circulation. At a low concentration, 35 kDa B-HA inhibited production of reactive oxygen species and tumor necrosis factor by neutrophils; at a higher concentration, 35 kDa B-HA promoted the migration of monocytes. Furthermore, 35 kDa B-HA significantly inhibited the migration of neutrophils with or without lipopolysaccharide treatment, suggesting that in local tissues, higher concentrations of 35 kDa B-HA have antiinflammatory effects. After 99mTc radiolabeled 35 kDa B-HA was intravenously injected into mice, it quickly entered into the spleen, liver, lungs, kidneys and other organs through the blood circulation.Conclusion: This study demonstrated that the HA fragment B-HA has good tissue permeability and antiinflammatory effects, laying a theoretical foundation for further clinical studies.Keywords: hyaluronic acid, 35kDa hyaluronic acid fragment, B-HA/HA35, molecular weight, inflammation, inflammatory cells, reactive oxygen species, injection safety